Teacher Online Informal Learning as a Means to Innovative Teaching During Home Quarantine in the COVID-19 Pandemic - Yu, Haiqin; Liu, Ping; Huang, Xiaoqing; Cao, Yuxi (Frontiers in Psychology, 2021)
The home quarantine in the COVID-19 pandemic has created challenges for teaching across the world and called for innovative teaching, as well as teachers’ learning. Given the rapid development of teachers’ online learning and teaching, identifying effective ways to facilitate innovative teaching under such challenging conditions is a critical issue. Although researchers have realized that workplace informal learning (IL) increasingly reveals its potential value to individual development, the relationship between IL and innovation has been under-explored. The purpose of this study was to evaluate the impact of IL on innovative teaching, through the mediating roles of three types of teaching-related efficacy, with a particular focus on college teachers and online context. A sample of 479 Chinese college teachers was randomly selected to participate in the survey. The results showed that teachers’ online IL in pandemic improved their personal teaching efficacy and ICT efficacy (information and communication technology efficacy), and then facilitated their innovative teaching without differences of gender and teaching-age effect. Whereas general teaching efficacy was not a mediator between online IL and innovative teaching. Hence, we proposed a can-do motivating model of teacher efficacy in fostering innovative teaching through informal learning. It implies three properties of teachers’ online IL: social interaction, autonomous learning and novelty-seeking. It also revealed that innovative teaching can be driven in COVID-19 pandemic, mainly by learning domain-specific knowledge and skills, thus enhancing personal teaching efficacy and ICT efficacy in online teaching context.